«The November Breakdown» («November Action») 1918: a Revolution or a Military Coup? - Monolatii, Ivan (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The purpose of the study is to analyze peculiarities of the historical event «The November Breakdown» («November Action») – the national democratic revolution in the Western Ukrainian lands – not as a revolution in its classical version, but a military coup with the elements of the national liberation struggle of Western Ukrainians in the autumn of 1918. On the basis of the historical and political analysis of the historiographical heritage concerning the preconditions and creation of the Western Ukrainian People’s Republic, the events of October 31 – November 1, 1918, are described as discrepancies and generalizations of their direct participants; the research also clarifies the factors of political and ideological «explanations» of the revolutionary «November Breakdown» in historiography of the Ukrainian diaspora of the 20th Century. The Soviet and contemporary Ukrainian historiography statements about the «revolutionary nature» of the events in Eastern Halychyna in 1918, and hence the November 1918 national democratic revolution, are still debatable. Halychyna Ukrainians made a legal proclaimation of the Ukrainian state within the framework of the Austrian-Hungarian state, they were waiting for a peaceful transfer of power in Eastern Halychyna, and the armed uprising of October 31 – November 1, 1918, became a military coup in the geopolitical realities of the rising tension in the Polish-Ukrainian relations. Therefore, on November 1, the Austro-Hungarian government authorized an act of transfer of the state power in Eastern Halychyna to the Ukrainian National Council, and on November 13, 1918, the Council proclaimed Western Ukrainian People’s Republic. The origins of the myth about the «revolutionary character», or «revolution» in Eastern Halychyna in 1918, are rooted in attempts to «inject» the non-existent in reality class struggle of the region population into the broader context of the Bolshevik and socialist revolution. During the Khrushchev Thaw, in 1957 this myth underwent certain modification in the famous article of historian O.Karpenko, and later on, in 1993, this myth transformation turned into a «national-democratic revolution» in Western Ukrainian lands. In fact, the memoirs of the participants and creators of the «November Action», the external sources, as well as the mass media of that, do not interpret the events under study just as “a revolution”, but only as “a coup”, “disarmament”, etc., which testifies to the militaristic nature of events.